2019
DOI: 10.3389/fpsyg.2019.00019
|View full text |Cite
|
Sign up to set email alerts
|

Denial and Empathy: Partners in Employee Trust Repair?

Abstract: Prior research on trust repair has focused primarily on investigating verbal responses to breaches of trust. Although consistently implicated in violations, the role of affect in the repair process has been mostly ignored. Using a scenario-based paradigm, we conducted an experimental study to examine the value of mistrusted party’s empathy, specific responses to an integrity-based violation (apology vs. denial), and nature of consequences (personal vs. organizational), as well as their interactive effects, on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…A number of experimental studies on the comparative effectiveness of different crisis response strategies, including apology and justification, have been conducted in crisis communication research. Except for two studies that found no significant differences between the two strategies (Bagdasarov et al, 2019;Kim & Harmon, 2014), previous experiments show that apology outperforms denial in repairing a company's image in the wake of a crisis (Cao et al, 2014;Kim et al, 2013;Schniter et al, 2013).…”
Section: Apologymentioning
confidence: 99%
See 2 more Smart Citations
“…A number of experimental studies on the comparative effectiveness of different crisis response strategies, including apology and justification, have been conducted in crisis communication research. Except for two studies that found no significant differences between the two strategies (Bagdasarov et al, 2019;Kim & Harmon, 2014), previous experiments show that apology outperforms denial in repairing a company's image in the wake of a crisis (Cao et al, 2014;Kim et al, 2013;Schniter et al, 2013).…”
Section: Apologymentioning
confidence: 99%
“…It plays a particularly important role in organizational trust repair, given the relative un-observability of companies' behavior (Fuoli et al, 2017). Recent studies have focused primarily on the role of apologies (Bagdasarov, Connelly, & Johnson, 2019;Ma et al, 2018). Apology and denial are two of the most fundamental and common strategies for remedying verbal trust repair strategies ( (Kim H. et al, 2004).…”
Section: Repairing Trustmentioning
confidence: 99%
See 1 more Smart Citation
“…There are seven studies examining leader ethics-based transgressions (mainly dishonesty), a relationship repair strategy (apology) and outcomes together (i.e., Bagdasarov, Connelly, & Johnson, 2019;Byrne et al, 2014;Grover & Hasel, 2015;Grover et al, 2019;Radulovic et al, 2019;Zheng, van Dijke, Narayanan, & De Cremer, 2018) and one study examining a task-focused transgression (incompetence), a relationship repair strategy (penance) and outcomes (Dirks et al, 2011). The vast majority of studies have examined the direct relationship between leader follower transgressions and outcomes.…”
Section: <Insert Table 2 Here>mentioning
confidence: 99%
“…All these actions not only stimulates cynicism but also reduces the level of trust. Bagdasarov, Connelly, and Johnson (2019) argue that many employees are cynical and have no faith in the change management process. Thus, managers need to involve all the stakeholders in the change management process.…”
Section: Employee Cynicism and Trustmentioning
confidence: 99%